Advices for Involving Parents in Childrens Learning Activities from School to Home - Alfiana Falan Syarri Auliya; Pujiyanti Fauziah (LPPM Universitas Pahlawan Tuanku Tambusai, 2021)
Parental involvement in childrens learning activities is important for the optimal of their growth and development. The aims of writing this article is to provide advices that can be applied in early childhood education institutions in terms of involving parents in children's learning activities at home. This article used the literature review method by reviewing recent literature such as books and research journals that provide an explanation of the topic of parental involvement in children's learning. In this research, several topics related to parental involvement are explained, including factors that influence and the type of parental involvement, forms of parental involvement in children's learning and advices for involving parents in children's learning activities. In short, this article is expected to help educators find strategies for involving parents to continue children's learning activities from school to home. Then, it is recommended for educators to use the results of this study, which is advices for involving parent in children's learning activities. Every parent must accompany the child's learning activities so that learning activities run effectively and can optimize the child's growth and development.